PENGARUH DUKUNGAN SUAMI TERHADAP KESEHATAN IBU HAMIL DI KELURAHAN PURO KARANGMALANG - Widy Nurwiandani; Sylvi Wafda Nur Amellia (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
The maternal mortality ratio, estimated at around 228 per 100,000 live births, has remained high at over 200 for the past decade, despite efforts to improve maternal health services and every hour one woman dies in childbirth or from pregnancy-related causes. Factors that cause maternal mortality can be broadly grouped into direct and indirect causes. The family has an instrumental support function, namely the husband's support given to meet the mother's physical needs with the help of the family, informational support in this case the husband has an instrumental support function, namely the husband's support given to meet the mother's physical needs with the help of the family, informational support, namely the husband's support in providing information he has obtained about pregnancy, assessment support, namely making the right decisions for his wife's pregnancy care, emotional support, namely the husband fully provides psychological support to his wife by showing concern and attention to her pregnancy and being sensitive to the needs and changes in the emotions of the pregnant woman. The purpose of this study was to determine the effect of husband's support on the health of pregnant women. This research method was designed with a cross-sectional approach with an observation form with a sample of 65 respondents. The results of the study showed that as many as 50 (76.9%) husbands supported pregnant women well, and there were 34 (52.3%) pregnant women who had good health status. P-Value of 0.004 <0.005, which means there is a significant relationship between husband's support and the health status of pregnant women.